2018 IEEE/CVF Conference on Computer Vision and Pattern Recognition 2018
DOI: 10.1109/cvpr.2018.00415
|View full text |Cite
|
Sign up to set email alerts
|

Beyond Grobner Bases: Basis Selection for Minimal Solvers

Abstract: Many computer vision applications require robust estimation of the underlying geometry, in terms of camera motion and 3D structure of the scene. These robust methods often rely on running minimal solvers in a RANSAC framework. In this paper we show how we can make polynomial solvers based on the action matrix method faster, by careful selection of the monomial bases. These monomial bases have traditionally been based on a Gröbner basis for the polynomial ideal. Here we describe how we can enumerate all such ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
67
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 50 publications
(68 citation statements)
references
References 45 publications
(95 reference statements)
1
67
0
Order By: Relevance
“…E.g., Pritts et al in [13], [15] were unable to reduce the degree of their constraint equations used for the H DES 222 lλ solver, which resulted in slow solver (see Table 4). Furthermore, stability sampling was required to generate useful solvers [46].…”
Section: Discussionmentioning
confidence: 99%
“…E.g., Pritts et al in [13], [15] were unable to reduce the degree of their constraint equations used for the H DES 222 lλ solver, which resulted in slow solver (see Table 4). Furthermore, stability sampling was required to generate useful solvers [46].…”
Section: Discussionmentioning
confidence: 99%
“…Experiments on synthetic data (see Section 5.1) revealed that using the standard GRevLex bases in the generator of [12] gave solvers with poor numerical stability. To generate stable solvers we used the recently proposed basis sampling technique from Larsson et al [16]. In [16] the authors propose a method for randomly sampling feasible monomial bases, which can be used to construct polynomial solvers.…”
Section: Creating the Solversmentioning
confidence: 99%
“…Recently, Larsson et al [16] sampled feasible monomial bases, which can be used in the action-matrix method. In [16] basis sampling was used to minimize the size of the solver. We modified the objective of [16] to maximize for solver stability.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…They then used this basis to construct an action matrix whose eigen-system returns the 64 complex solutions of the problem. Later work by Larsson et al [21,22], inspired by [19], introduced an automatic generator of action matrices, which they applied to Stewenius et al's formulation.…”
Section: Related Workmentioning
confidence: 99%